Student courses management plan - Mohamad Azrul Amin, Mohamed Asof (2014)
Planning is a matter that will not run from everyone life, it include students. Students always make plan for whatever they do. Does something without planning may cause the outcome not as expected. All students in UMP have the power to control their study course path. But not all the student uses it with well and organized. It will become more problem to the student if they have fail subject in their course study. With this study, a system will be developing where it enables student to plan and manage their courses path systematically during their study. During the development the system, the Iterative and Incremental Development model will be used as a guideline for the process phases. The system will be a web base application where it will use the apache server and SQL for database language. This study expected will be successful systems that help students in manage their course path. To conclude it all, students can enjoy their campus life with the extra-curricular without worry as their plan of the course study is establish.